Immunoglobulin G4-Related Disease Presented as Recurrent Otitis Media and Mixed Hearing Loss Treated With Cyclophosphamide and Rituximab: A Case Report - Shao SAN; Chia-der LIN; Sheng-ta TSAI; Chao-chun LIN; Po-chang WU (Archives of Rheumatology, 2019)
Immunoglobulin G4-related disease (IgG4-RD) is a systemic autoimmune disease; however, it rarely presents as recurrent otitis media and mixed hearing loss. In this article, we present a 43-year-old male patient who presented with recurrent otitis media and mixed hearing loss that is the 12th case of IgG4-RD with middle and inner ear involvement. We also report the clinical response of cyclophosphamide and rituximab therapy in IgG4- RD. These two drugs have never been used to treat otologic symptoms, but were used to treat other organs affected by IgG4-RD. One year later, the patient underwent mastoidectomy of the right ear and the pathological reports revealed IgG4-related disease. A rheumatologist administered immunosuppressive therapy comprising cyclophosphamide and rituximab. After therapy, patient’s right-sided mixed hearing loss partially improved. We recorded all pure tone audiometry data to evaluate the clinical course and treatment effect. Finally, we concluded that pathological confirmation and further immunosuppressive therapy should be considered in a timely manner to prevent hearing impairment. We recommend cyclophosphamide and rituximab for the treatment of diseases involving the middle and inner ear.